LAWYER’S RIGHTS AS A REPRESENTATIVE IN ADMINISTRATIVE JUDICIARY AND THEIR CLASSIFICATION - Husseinli, Alaskar (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the article considers and analyzes the rights of a lawyer as a representative in administrative proceedings, provided by current legislation of Ukraine and carries out their classification. Methods: the study was conducted using such methods as analysis, synthesis, comparison. Results: it is concluded that the list of professional and procedural rights of a lawyer in administrative proceedings is quite wide. However, today there are no effective mechanisms and procedures for a lawyer to exercise his rights in practice. Discussion: problems of legislative definition and practical use of a lawyer’s rights as a representative within administrative proceedings. The main features of a democratic and independent state are the rule of law and justice. One of the types of justice in our state is administrative justice, where the activity of administrative courts is provided to consider administrative cases and resolve administrative disputes. The main tool for the protection of human rights, freedoms and legitimate interests is administrative justice, which aims to ensure and comply with the principles of legality by the executive and local authorities. In order to protect and represent the interests of a person in administrative and public legal relations at the legislative level in Article 16 of the CAS of Ukraine dated 06.07.2005 №2747-IV it was stipulated that representation in court, as a type of legal aid, is carried out exclusively by a lawyer (professional legal aid), except as provided by law. Free legal aid is provided in the manner prescribed by law governing the provision of free legal aid. In this case, a lawyer is a person who participates in administrative proceedings in a particular administrative case, as well as a person who has the right to apply to any government agency or court on behalf and in the interests of the client he represents. The rights of a lawyer are the basis of his legal status, so determining their list and classifying them is an important issue.